Aggregation‐Induced Emission (AIE) Fluorophore Exhibits a Highly Ratiometric Fluorescent Response to Zn2+ in vitro and in Human Liver Cancer Cells. Issue 53 (1st August 2017) - Mehdi, Hassan; Gong, Weitao; Guo, Huimin; Watkinson, Michael; Ma, Hua; Wajahat, Ali; Ning, Guiling
Abstract: Two novel organic fluorophores, containing bis‐naphthylamide and quinoline motifs, have been designed and synthesized. One of the fluorophores contains an isobutylene unit and exhibits a significant aggregation‐induced emission (AIE) and a remarkable highly selective ratiometric fluorescence response towards Zn 2+ in solution as well as in human liver cancer cells. The AIE behavior of this fluorophore was fully verified by fluorescence and UV/Vis spectroscopy, quantum yield calculations, and single‐crystal X‐ray diffraction, which revealed an intricate crystal packing system. Conversely, a fluorophore that lacks the isobutylene moiety did not exhibit any significant fluorescent properties as a result of its more flexible molecular structure that presumably allows free intramolecular rotational processes to occur. Abstract : Let it shine : A novel fluorophore8AQ containing an isobutylene unit exhibits a significant AIE feature and remarkable ratiometric response to Zn 2+ in solution as well as intracellular bio‐imaging behavior in human liver cancer cells. Conversely, fluorophore8WB, which lacks the isobutylene moiety did not exhibit any significant fluorescent properties as a result of its more flexible molecular structure.